Description of three new Tetranchyroderma gastrotrichs (Macrodasyida: Thaumastodermatidae) from South Korea - Lee, Jimin; Kim, Dongsung; Chang, Cheon Young (Zootaxa, 2013)
The present paper deals with description of three new marine gastrotrich species belonging to the genus Tetranchyroderma with a new record for Korea of T. schizocirratum Chang, Kubota & Shirayama, 2002, on the basis of specimens from the Korean coast. Tetranchyroderma anisoankyrum sp. nov. is differentiated from congeners by its dorsal cuticular armature of pentancres with central tine longer than the others, a pair of rod-like cephalic tentacles, 2 cirratum-type TbDL, 13–14 cirratum-type TbL per side, and a pair of TbL. Tetranchyroderma coreense sp. nov. is distinguished from other pentancrous species by cirratum-type tubes of 2 TbDL, one TbL, 3–4 TbVL, paired foot-type TbV, and absence of cephalic tentacles. Tetranchyroderma oblongum sp. nov. is characterized by the character combination of cuticular armature of tetrancres, 7 dorsolateral and 7–9 lateral cirratum-type tubes, and 33–38 TbVL along whole body. This brings the total number of species in the genus Tetranchyroderma known from South Korea to 12.